HUBUNGAN KONDISI TERUMBU KARANG DENGAN KELIMPAHAN IKAN KARANG TARGET DI PERAIRAN PULAU TINABO BESAR, TAMAN NASIONAL TAKA BONERATE, SULAWESI SELATAN - Ghiffar, Muhammad Albar; Irham, Andi; Harahap, Syawaludin A.; Kurniawaty, Nia; Astuty, Sri (Jurnal Ilmu Kelautan SPERMONDE, 2017)
This research aims to understand the condition of coral reef (life coral), the abundance of reef target fishes, and the corellation between those two variables. This research has been conducted in Tinabo Besar Island with 6 sampling stations in 5-6 meter depth. Data collected are substrate cover precentage (life form), and the number of reef target fish appeared from 7 specified families (Serranidae, Lutjanidae, Haemulidae, Lethrinidae, Scaridae, Siganidae, and Acanthuridae) using Underwater Photo Transect (UPT) and Underwater Visual Census (UVC). Substrate cover analyzed using CPCe software with life coral, dead coral, algae, abiotic, and other biota cover output. Mortality Index (MI) obtained from the ratio of life coral and dead coral. The result shows that percentage of life coral coverlie between 11.87% to 38.80%, with dominance of Coral Masive (CM). It’s mean that the coral reef condition is in poor to moderate category. Coral death ratio is low with MI between 0.15 to 0.30. Reef target fish total abundance is 493 individual/2100m2 from 31 species, with dominance from Lutjanidae family (173 individual). The result shows positive and strong enough correlation between coral reef coverage and reef target fish abundance (r=0.65) with Determinantion Coefficient at 42.55%. Linear regression is y=-12.929+3.7562x, where in every addition of coral reef cover percentage, resulted in addition of 4 fishes.Keyword: life coral, abundance, reef target fish, correlation, Tinabo Besar Island